Health education to promote healthy aging with elderly patients at a referral center for social assistance (CRAS) in Sinop-MT - Iori, J. O.; Dullius, J. L.; Alves, M. A. P. (Scientific Electronic Archives, 2017)
Nursing care for the elderly should aim to promote elderly health and reduction of foreseeable risk factors, as well as value and institute measures to the greatest possible degree of autonomy and independence in the elderly in relation to his life and especially about his Cheers. With this view, we carried out a study with 16 members aged from Linkages Strengthening Group of a Social Assistance Reference Center (CRAS), the municipality of Sinop - MT, to enhance understanding of the elderly as the promotion of health through education about risk and protective factors of the most common diseases and health problems among the elderly. We used the action research as a methodological reasons, because this means turning the subject both at the level of thought and in action. The results of this research showed a female predominance in the participation of older age groups, increased participation of older widows with education of 01 years to 04 years. The perception of the elderly as the educational activity performed was satisfactory, reporting that the dynamics of the talks were good, important and promoted new information. It was also found through most of the elderly respondents reported the need for health education activities for this audience. It is concluded that the elderly incorporated into their daily health promotion measures learned in the educational activity, with improvements in quality of life. As well, the need to implement more health education programs for the elderly aimed at promoting healthy aging.